Moldova Preschool and General Education : Transitioning to a Decentralized Service Delivery Model - World Bank Group (World Bank, Washington, DC, 2018)
Moldova’s public expenditures on education as a share of GDP and total public sector spending are higher than in most countries in the European Union (EU) and the Organization for Economic Cooperation and Development (OECD). Moldova’s challenges to improve the quality and efficiency of education provision need to be addressed in a context of declining student numbers, and persistent inequities between population groups. This report identifies key challenges to the adequate delivery of pre-school and general education related to the decentralized governance mechanism. They relate both to the (de jure) regulatory framework that spells out the mandates of national and local level administrations and school management, and to (de facto) weaknesses in the implementation of these mandates. These challenges are summarized. The remainder of this section further describes the key challenges, and recommends policy directions and areas for further analysis to support evidence-based decision-making in the future. These recommendations are also summarized at the end of this chapter.